The Effect of Modification Methods on Physicochemical and Sensory Quality of Purple Corn Flour - Tartilla, Fahniati Sofi; Nurfatimah, Ratna Palupi; Astuti, Nugrahani; Ahmi, Hanif Naufal (Universitas Negeri Padang, 2025)
Purple corn flour (Zea mays L.) is a local food ingredient rich in anthocyanins with potential as a functional commodity. However, its basic qualities such as moisture content and color stability are strongly influenced by modification methods. This study aimed to evaluate the effects of pregelatinization, fermentation using Lactobacillus casei, and their combination on the physicochemical (moisture content and color parameters L*, a*, b*) and sensory qualities of purple sticky corn flour. All treatments were analyzed through hedonic testing with 30 semi-trained panelists and laboratory evaluation. Data were statistically analyzed using ANOVA followed by Duncan’s test at a 5% significance level. The results showed that among all treatments, pregelatinization produced the lowest moisture content (9.88%) compared to the control (11.05%) and improved color intensity (lower L* and b* values, higher a* value). Fermentation alone tended to reduce aroma acceptance, while the combination treatment provided intermediate results. Sensory evaluation confirmed that pregelatinization was the most preferred method, maintaining neutral aroma and enhancing visual appeal. These findings highlight pregelatinization as the most effective modification technique, providing purple corn flour with better stability, storage quality, and visual attributes, thus supporting its potential as a raw material for value-added functional food products.